Praxeology Concept: Investigating the Actions of Primary School Teachers in Achieving Arabic Teaching - Anwar Sanusi; Mahfuz Rizqi Mubarak; Abdulkhaleq Al-Rawafi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2022)
This study presents the results of an investigation of Arabic teachers' actions at the primary school level in achieving the objectives of teaching and learning Arabic. This study used a descriptive qualitative approach with two data collection techniques: observations and interviews. The collected data then were analyzed using a didactic anthropological theory based on three main components: the teachers' desire (want) to act, the means or methods used by the teachers, and the results or objectives (end) achieved by the teacher's actions. The results of this study showed that first, Arabic teachers had a strong desire to overcome the problems faced by the students, especially in the demotivating aspect of studying Arabic. Second, from the results of those desires, the Arabic teachers determined and used several methods such as presenting the materials using songs, cartoon videos and integrating Islamic religious knowledge. Third, the actions or methods used by the Arabic teachers resulted in positive outcomes in teaching and learning Arabic for students at the primary school level.